G cell population of the gastric antrum, plasma gastrin, and gastric acid secretion in patients with and without duodenal ulcer. Issue 8 (August 1978) - Royston, C M; Polak, J; Bloom, S R; Cooke, W M; Russell, R C; Pearse, A G; Spencer, J; Welbourn, R B; Baron, J H
Abstract : Estimates of the G cell population were made in 24 resected human pyloric antra from counts of cells in multiple samples and from measurements of antral size. Measurements had been made previously in 20 subjects of acid output (basal and after pentagastrin) and in 10 subjects of plasma gastrin (basal and after insulin + bicarbonate). G cells were most dense near the pylorus, but their circumferential distribution was even. The G cell populations ranged from 8 to 15 (mean 10) million in four control patients and from 3 to 43 (mean 18) million in 15 patients with duodenal ulcer. Those with recurrent ulcer after vagotomy had either a low G cell count and incomplete vagotomy, or a high G cell count and apparently complete denervation. Two patients with hypergastrinaemia and duodenal ulcer had moderate (29 X 10(6)) or marked (56 X 10(6)) excesses of G cells. 'G cell hyperplasia' may represent the extreme end of the normal range of G cell numbers in the antrum, and can be assessed by semi-quantitative grading of G cell hyperplasia in antral biopsies. There were significant direct correlations between antral area and G cell density, between peak acid output and G cell population, and between basal plasma gastrin and G cell density (but not population). We suggest that, in patients with duodenal ulcer, acid and gastrin secretion are interrelated and that both are related to the masses of parietal cells and of G cells.